Marsupialization: A conservative approach for treating dentigerous cyst in children in the mixed dentition - Kirtaniya B (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2010)
Dentigerous cysts are usually encountered in the practice of pediatric dentistry. The treatment modalities range from marsupialization to enucleation of the lesion and are based on the involvement of the lesion with the adjacent structures. However, loss of a permanent tooth in the management of a dentigerous cyst can be devastating to a child who has already a congenitally missing tooth. The first case describes the technique of marsupialization in which we extracted the grossly carious deciduous 1st molar and created a window through the extracted socket to decompress the lesion. In this case the 2nd premolars were congenitally missing on both sides of the mandible for which we had not gone for enucleation of the dentigerous cyst along with the developing 1st premolar. The second case is a developmental type of a big dentigerous cyst where marsupialization was followed by enucleation of the cystic lining but without removal of the affected tooth. Both the teeth erupted in the oral cavity.